Sensitivity and resistance level of sourgrass population subjected to glyphosate application - Cavalieri, Jhonatan Diego [UNESP]; Nascentes, Renan Fonseca [UNESP]; Negrisoli, Matheus Mereb [UNESP]; Carbonari, Caio Antonio [UNESP]; Raetano, Carlos Gilberto [UNESP] (Polish Academy of Sciences Chancellery, 2021)
The intensive use of glyphosate in agricultural areas has increased the frequency of weeds that are resistant to herbicides. Thus, this study was aimed to assess the sensitivity and resistance level of Digitaria insularis (L.) Fedde (sourgrass) populations to glyphosate. Sixtytwo sourgrass populations were collected from the states of Parana and Sao Paulo, Brazil, and subjected to glyphosate application at 1,080 and 2,160 g of acid equivalent (a.e.) ? ha-1 in screening assays. Five sourgrass populations were selected, three of which are resistant and two of which are susceptible to glyphosate, to determine the resistance factors (RFs) through dose-response studies at two phenological stages of plant growth: The 2-4-leaf stages and the 2-4-Tiller stage. The trials were conducted in a greenhouse in accordance with a completely randomized design. In both trials, the control was evaluated based on the score of the visual control symptoms (VC) and the percentage of dry matter (DM) in relation to those of the control (without application). In the screening test, the data obtained for the response variables were adjusted for frequency curves by following the regression model proposed by Gompertz. The results indicated low sensitivity of D. insularis to glyphosate in 100% of the samples from areas in which soybeans are tolerant to this herbicide. Populations with susceptible plants were found in fallow areas, pasture areas and sugar cane fields. Based on the values of VC50 and DM50, the maximum RF obtained among the populations was 15. More advanced stages of development make sourgrass control difficult, requiring doses that are 3.5 times greater than those at the initial stage.
Keywords: chemical control; Digitaria insularis; Gompertz model; resistance factor